Pola Sebaran Kepiting Bakau Dengan Alat Tangkap Bubu Di Perairan Payau Sungai Tanjung Keramat Kecamatan Banda Mulia Kabupaten Aceh Tamiang - Faisal Syahputra; Safrizal Safrizal; Chaliluddin Chaliluddin (Jurnal TILAPIA, 2021)
Mud crab (Scylla spp.) is a fisheries commodity that is able to adapt strongly to mangrove forests and has a wide distribution area. The wide spread of mud crab is due to the fact that mud crab have a wide tolerance to abiotic factors, especially temperature and salinity. This study aims to determine the composition of the catch and the distribution pattern of mud crab (Scylla spp.) in the waters of the Gampong Tanjung Keramat River, Banda Mulia District, Aceh Tamiang Regency. Sampling was carried out randomly using purposive sampling method at three observation stations including Station 1 (mangrove ecosystem in the river mouth), Station 2 (in the middle of river in the mangrove ecosystem), and Station 3 (in the middle of the mangrove ecosystem). The results showed that the mud crab that were caught using traps consisted of one species, Scylla serrata, with the ratio of male and female mud crab yield is 1.5: 1 (6 males and 4 females). The body size of mud crab varies with the length range of male mud crab, namely 5.2 cm - 8.1 cm, the length of female mud crab is 5 cm - 7 cm. While the range of male mud crab widths is 6.7 cm - 9.6 cm, the width of female mud crab is 5 cm - 8.8 cm. The body weight of male mud crab is 80 g - 350 g, while the body weight of female crab is 90 g - 150 g. Distribution pattern of Scylla spp. located in 3 locations with 9 points of trap/ bubu operation spread over 3 stations. The distribution locations of mud crab are: mangrove ecosystem, river flow in the middle of mangrove ecosystem, and in the middle of river flow of mangrove ecosystem.